EMPIRICAL RESEARCH OF LEVELS OF FORMING THE GENERIC COGNITIVE EDUCATIONAL ACTIVITIES OF STATEMENT AND SOLUTION OF PROBLEMS IN JUNIOR SCHOOL CHILDREN - Alekseeva, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article deals with one of the urgent problem to identify the quality of educational activities. In order to solve this problem it presents the author’s method of determinationthe levels of forming the generic cognitive educational activities of statement and solution of problems in junior school children. Substantive characteristic of each diagnostic task is givento support the structure of the generic cognitive educational activities of statement and solution of problems in junior school children. The researches, the analysis of its results have generated data on possible levels of forming the generic cognitive educational activities of statement and solution of problems in junior school children.